Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Matematika Diskrit - Kurnia, Ulfa Isni; Lathifah, Afra; Rizki, Fahlul; Alfina, Alfina (Universitas Lampung, 2024)
Discrete mathematics learning is an important part of higher education, especially in the context of computer science and information technology. Several studies have shown that many students face difficulties in solving complex mathematical problems, which constitute a significant challenge in the learning process. Therefore, it is important to apply a comprehensive learning approach and pay attention to student needs, because this can help overcome weaknesses related to understanding discrete mathematics and improve interest or motivation. The results of this research highlight the potential of the Discovery Learning model as an effective approach in improving discrete mathematics learning. The practical implication of this research is that integrating the Discovery Learning model in discrete mathematics learning design can increase student engagement and their academic achievement. Thus, future studies could further explore the long-term impact of implementing this model or compare it with the use of other learning approaches.